1976
DOI: 10.1520/jfs10505j
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Powder Tattooing of the Skin

Abstract: Determination of the distance from muzzle to victim from the appearance of a gunshot wound in the skin is often of great importance. Such information may be necessary to confirm or disprove an account of the circumstances surrounding a death due to firearms. Contact wounds generally can be recognized by the presence of soot and powder in and around the wound as well as searing of the skin from the flame. When the contact wound overlays bone, tearing of the skin or muzzle imprints may be present. Intermediate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Due to a better aerodynamic form, ball powder can travel further at a greater velocity, enabling deposits on the skin at a greater range [5]. To determine the firing distance by the size and the density of the gunpowder residue pattern and also the maximum distance at which the powder residue pattern is left on the target surface or powder tattooing of the skin takes place, it is very important to consider the physical form of the propellant [1,5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a better aerodynamic form, ball powder can travel further at a greater velocity, enabling deposits on the skin at a greater range [5]. To determine the firing distance by the size and the density of the gunpowder residue pattern and also the maximum distance at which the powder residue pattern is left on the target surface or powder tattooing of the skin takes place, it is very important to consider the physical form of the propellant [1,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing the differences between the measurements of the powder tattoo pattern on animal bodies and on a blotter paper Di Maio et al [5] found that they had measured the main powder pattern and ignored the ''flyers,'' while the criminalists had measured the entire pattern, including the flyers.…”
Section: Discussionmentioning
confidence: 99%
“…The injuries caused by gunpowder particles are generally confined to superficial layers of the epidermis. Depending of the physical form of the powder and a number of other variables, gunpowder may penetrate into the upper layer of the dermis [10,11] or more deeper into the stratum reticulare of the dermis [4]. The soot particles not only deposit on the surface of the skin, but can also be found in the epidermis and sometimes in the stratum papillare of the dermis [4].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed solution for test firings was to use various simulant materials. Recommendations for those materials were based on the studies comparing those materials to the skin of some animals, like rabbits or pigs [27]. The conclusions of this work were that blotter paper is an acceptable skin simulant at ranges less than 18 in.…”
Section: Human Body As a Targetmentioning
confidence: 99%